Short‐Term Isocaloric Intake of a Fructose‐ but not Glucose‐Rich Diet Affects Bacterial Endotoxin Concentrations and Markers of Metabolic Health in Normal Weight Healthy Subjects - Nier, Anika; Brandt, Annette; Rajcic, Dragana; Bruns, Tony; Bergheim, Ina (Molecular nutrition & food research, 2019)
Scope Dietary pattern and impairments of intestinal barrier function are discussed to be critical in the development of metabolic impairments. Here, it is determined if an isocaloric exchange of complex carbohydrates with monosaccharides affects markers of intestinal permeability and metabolic health in healthy subjects. Methods and Results After a dietary standardization for 4 days, all 12 subjects aged 21–33 years receive an isocaloric fructose‐ and glucose‐enriched diet for 3 days separated by a wash‐out phase. Anthropometry, blood pressure, markers of intestinal permeability and metabolic as well as inflammatory parameters are determined in blood samples or isolated peripheral blood mononuclear cells collected at baseline, after standardizations and the monosaccharide interventions, respectively. While anthropometric and inflammatory parameters are not changed, the intake of an isocaloric fructose‐ but not glucose‐enriched diet is associated with a significant increase of bacterial endotoxin plasma levels and alanine aminotransferase activity in serum, while total plasma nitrate/nitrite concentrations are significantly decreased. In peripheral blood mononuclear cells, Toll like receptors 4, 2, and MYD88 mRNA expressions are significantly induced after the fructose‐rich but not the glucose‐rich diet. Conclusion In metabolically healthy subjects, even a short‐term intake of a fructose‐rich diet can elevate bacterial endotoxin levels and change markers of liver health and vascular endothelial function. The intake of a high‐fructose diet (25% of total energy) for 3 days leads to elevated bacterial endotoxin (LPS) levels, elevated alanine aminotransferase (ALT) activity in serum, and lower plasma total nitrate/nitrite (NOx) levels in healthy young adults. Similar changes are not found for a glucose‐rich diet.